Immunosuppression Affects Neutrophil Functions: Does Calcineurin-NFAT Signaling Matter? - Vymazal, Ondřej; Bendíčková, Kamila; De Zuani, Marco; Vlková, Marcela; Hortová-Kohoutková, Marcela; Frič, Jan (Frontiers in Immunology, 2021)
Neutrophils are innate immune cells with important roles in antimicrobial defense. However, impaired or dysregulated neutrophil function can result in host tissue damage, loss of homeostasis, hyperinflammation or pathological immunosuppression. A central link between neutrophil activation and immune outcomes is emerging to be the calcineurin-nuclear factor of activated T cells (NFAT) signaling pathway, which is activated by neutrophil detection of a microbial threat via pattern recognition receptors and results in inflammatory cytokine production. This potent pro-inflammatory pathway is also the target of several immunosuppressive drugs used for the treatment of autoimmune disorders, during solid organ and hematopoietic cell transplantations, and as a part of anti-cancer therapy: but what effects these drugs have on neutrophil function, and their broader consequences for immune homeostasis and microbial defense are not yet known. Here, we bring together the emerging literature describing pathology- and drug- induced neutrophil impairment, with particular focus on their effects on calcineurin-NFAT signaling in the innate immune compartment.